Barriers and Facilitators to Involvement in Children's Diabetes Management Among Minority Parents. (29th January 2020) - Butler, Ashley M; Hilliard, Marisa E; Titus, Courtney; Rodriguez, Evadne; Al-Gadi, Iman; Cole-Lewis, Yasmin; Thompson, Deborah
Abstract: Objective: This study aimed to describe parents' perceptions of the factors that facilitate or are barriers to their involvement in children's type 1 diabetes (T1D) management among African American and Latino parents. Methods: African American and Latino parents ( N = 28) of 5- to 9-year-old children with T1D completed audio-recorded, semi-structured interviews that were transcribed and analyzed using thematic analysis. Themes were identified that aligned with the theoretically-derived Capability–Opportunity–Motivation–Behavior (COM-B) framework. Results: Parents described Capability-based facilitators of parent involvement, including positive stress management, religious/spiritual coping, organizational/planning skills, and diabetes knowledge. Capability-based barriers included child and parent distress. Interpersonal relationships, degree of flexibility in work environments, and access to diabetes technologies were both Opportunity-based facilitators and barriers; and Opportunity-based barriers consisted of food insecurity/low financial resources. Parents' desire for their child to have a "normal" life was described as both a Motivation-based facilitator and barrier. Conclusions: African American and Latino families described helpful and unhelpful factors that spanned all aspects of the COM-B model. Reinforcing or targeting families' unique psychological, interpersonal, and environmental strengths and challenges in multilevel interventions has potential to maximize parental involvement in children's diabetes management.